PENGUATAN LITERASI BUDAYA LOKAL BAGI GURU RA DI KECAMATAN SOKO TUBAN - Roudlotun Ni'mah; Endang Puspitasari; Ahmad Muthi' Uddin; Putri Nedike Hernayanti (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service initiative addresses the limited integration of local cultural content in early childhood education. The primary objective is to enhance cultural literacy among young children by empowering PAUD (early childhood education) teachers in Kecamatan Soko through the utilization of a localized cultural encyclopedia as an innovative learning medium. The method employed was a participatory approach involving socialization and training sessions, where teachers were actively engaged in utilizing and integrating the encyclopedia into their lesson plans and classroom activities. The results indicate a significant increase in teacher understanding and enthusiasm for incorporating local culture into their teaching practices. This initiative not only strengthens teachers' capacities but also fosters the development of cultural awareness and appreciation among early learners.